Animal Venom Peptides Cause Antinociceptive Effects by Voltage-gated Calcium Channels Activity Blockage - Trevisan, Gabriela; Oliveira, Sara M. (Current Neuropharmacology, 2022)
Pain is a complex phenomenon that is usually unpleasant and aversive. It can range widely in intensity, quality, and duration and has diverse pathophysiologic mechanisms and meanings. Voltage-gated sodium and calcium channels are essential to transmitting painful stimuli from the periphery until the dorsal horn of the spinal cord. Thus, blocking voltage-gated calcium channels (VGCCs) can effectively control pain refractory to treatments currently used in the clinic, such as cancer and neuropathic pain. VGCCs blockers isolated of cobra Naja naja kaouthia (α-cobratoxin), spider Agelenopsis aperta (ω-Agatoxin IVA), spider Phoneutria nigriventer (PhTx3.3, PhTx3.4, PhTx3.5, PhTx3.6), spider Hysterocrates gigas (SNX-482), cone snails Conus geographus (GVIA), Conus magus (MVIIA or ziconotide), Conus catus (CVID, CVIE and CVIF), Conus striatus (SO- 3), Conus fulmen (FVIA), Conus moncuri (MoVIA and MoVIB), Conus regularis (RsXXIVA), Conus eburneus (Eu1.6), Conus victoriae (Vc1.1.), Conus regius (RgIA), and spider Ornithoctonus huwena (huwentoxin-I and huwentoxin-XVI) venoms caused antinociceptive effects in different acute and chronic pain models. Currently, ziconotide is the only clinical used N-type VGCCs blocker peptide for chronic intractable pain. However, ziconotide causes different adverse effects, and the intrathecal route of administration also impairs its use in a more significant number of patients. In this sense, peptides isolated from animal venoms or their synthetic forms that act by modulating or blocking VGCCs channels seem to be a relevant prototype for developing new analgesics efficacious and well tolerated by patients.
Keywords: nociception